Development of integrated loose fruit collector machine for oil palm plantations - Mohd Zulfahmi Mohd Yusoff; A. Zamri; M. Z. A. Abd Kadir; W. Z. Wan Hassan; N. Azis (Bulletin of Electrical Engineering and Informatics, 2020)
Oil palm loose fruit have always been part of oil palm harvesting operation. The current manual loose fruit collection by hand picking or raking is contributing to the minimum productivity and large amounts of debris. Effort in future shall be explored for the potential machine or system to collect the loose fruit in the field with the result of clean loose fruit. A new machine for loose fruit collection is being developed and examined which knows as integrated oil palm loose fruit collection machine for collecting loose fruit from the palm base. Consist of three main integrated stages; the suction stage is used to collect the loose fruit, followed by segregating stage, which used to segregate the loose fruit from debris through double layer rotating drum and unloading stage of loose fruit to the 3-4 metric tons bin by using hydraulic tipping cylinder. Result indicates that at least more than 50% productivity of loose fruit collection were increased. In addition, the clean loose fruit collection resulted with the debris less than 10%. Hence, with this development, better quality loose fruits are collected with minimum debris for further processing in the palm oil mill, which will contribute to better oil extraction rate.